Closing rice yield gaps in Africa requires integration of good agricultural practices - Senthilkumar, Kalimuthu (Elsevier, 2022)
Despite decades of international research and development efforts focusing on increased rice production in Africa, there is large yield gap, and the local production still needs to be complemented by rice imports to meet consumption demands. This paper aims to provide an overview of published research findings on rice yield gaps and the effects of ‘good agricultural practices’ (GAPs) on rice yield and nutrient use efficiency. The majority of previous studies were from irrigated lowlands, and quantified rice yield gaps as farmer-based (difference between ‘actual yield’ and ‘best farmers’ yield’) and model-based yield gaps (difference between ‘actual yield’ and ‘potential yield for irrigated and water-limited potential yield for rainfed rice’). The mean farmer- and model-based yield gaps were 3.1 and 5.0 t ha–1 for irrigated lowland (IL); 3.1 and 7.7 t ha–1 for rainfed lowland (RL); 2.0 and 6.0 t ha–1 for rainfed upland (RU), respectively in Africa. An analysis of studies from literature on GAPs in Africa revealed that most studies (64 %) were from IL and a wide range of yield increases following individual components of GAPs across environments. A median yield increase of 1.0 t ha–1 was achieved with improved water conservation practices in IL, whereas improved weed management increased yields by 0.7 t ha–1, mainly in IL compared to farmers’ practices. Application of inorganic fertilizers and/or organic amendments increased the yield by 0.8–1.2 t ha–1 across the environments. Integration of GAPs increased the median yield by 2.1 and 1.5 t ha–1 in IL and RL, respectively. The calculated agronomic efficiency of N, P and K from fertilizer experiments were within the desirable levels mainly in the IL and RL environments and comparable to the values from similar environments in Asia. For instance, the agronomic efficiency of N was 21, 13 and 12 kg kg–1, respectively for IL, RL and RU in Africa. Although rice yield gaps in Africa can be substantially reduced by introduction of integrated GAPs to farmers, there is large difference between model-based yield gaps and yield gain obtained by integrated GAPs. Further efforts are needed to identify factors causing this difference. We recommend a research and development focus on rainfed lowland rice systems, which have the largest model-based yield gaps by partially converting them to irrigated systems, and on improving nutrient use efficiencies and closing nutrient cycles.